(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article talks about the methodology of teaching foreign languages in Uzbekistan.The author, relying on philological data and written sources, studied the existingpeculiarities on the subject, which made clarifications on the basis of existing scientific literature.